SME Readiness Towards Digitalization in Malaysia - Tham, Kai Wen; Atan @ Yaakub, Siti Anisah (Research in Management of Technology and Business, 2021)
Malaysia Government through Ministry of Finance (MOF) allocated RM500 million in Budget 2020 to digitalize SMEs operation. Digitalization engagement is one of the challenges that SMEs are facing today. SMEs need to remain competitive and prepare for the digitalization and able to respond the current social challenges, regulatory, technological and economic, optimize the scope of digitalization, and take advantage of new growth opportunities. Therefore, the purpose of this study is to determine the readiness of SMEs from the aspects of infrastructure & technology, human capital, information security concern, top management commitment and resistance to change before embarking on digitalization. The scope of this study covers manufacturing SMEs in the Northern Region which is Perak Region. Data was collected from 200 respondents from the manufacturing sector of SME in Perak by using online survey. Descriptive analysis was carried out in this study. The overall digital readiness suggests that SMEs in Perak are ready to embark on the e-business journey. However, the readiness to adopt digitalization can still be improved. Further study could be obtaining a larger sample size of potential results from all states from Malaysia, which could be important for generalizing the readiness of SMEs. This study has merit in the sense that it can help the manufacturing SME to adopt digitalization and improve their readiness factors at the SMEs continuously.